Drop Spreading and Evaporation on a Heated Substrate Under Variable Gravity Conditions; 15th International Heat Transfer Conference (IHTC-15) - Kabov O. A. Oleg Aleksandrovich; Zaytsev D. V. Dmitry Valerjevich; Gatapova E. Ya. Elizaveta Yakovlevna; Semenov A. A. Andrey Aleksandrovich; Bykovskaya E. F. Elena Fedorovna; Karnaukhova E. N. Ekaterina N.; Ajaev V. S. Vladimir Sergeevich; Feoktistov D. V. Dmitriy Vladimirovich; Kuznetsov G. V. Geny Vladimirovich (2014, 2014)
Title screen